Application of Finite Element Analysis For Prediction of Disc Brake Squeal - Hassan, Muhammad Zahir; Mohd Irwan, Mohd Azmi; Abdul Munir, Fudhail (World Academic Union (World Academic Press), 2011)
Automotive disc brake squeal has been a major concern in warranty issues and a challenging problem for many years to automotive industry. In order to tackle this problem, a variety of tools have been developed which include both experimental studies and numerical modeling technique. This paper investigated the brake squeal by using Finite Element Analysis (FEA). Using modal analysis, the dynamic deflection pattern of the disc brake is resolved into a set of simple mode shapes each having a unique natural frequency. In the numerical free-free modal analysis, mesh density and material properties of the components are adjusted to obtain similar natural frequencies to those measured experimentally. The outcomes of the FEA are presented in terms of the extracted natural frequencies and the associated mode shapes. This approach is therefore can be used as a predictive tools to evaluate disc brake squeal for automotive applications.